Office building maintenance: Cost prediction model - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Croatian Society of Civil Engineers, 2013)
Building maintenance costs are increasing rapidly due to poor maintenance in the past. In this paper, attempts are made to identify the characteristics of scheduled maintenance. It has been established that the characteristics of scheduled maintenance always affect the cost performance. Therefore, this research aims to establish their relationships. Then, regression model is produced for maintenance prediction purposes. The triangulation approach that includes literature review, questionnaire survey, and interviews, has been adopted for data collection. Consequently, the regression model can be adopted by practitioners.